2017
DOI: 10.1097/cej.0000000000000252
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and the risk of hepatocellular carcinoma and chronic liver disease: a systematic review and meta-analysis of prospective studies

Abstract: An inverse association has been reported between coffee drinking and the risk of hepatocellular carcinoma (HCC) and chronic liver disease (CLD), but its magnitude is still unclear. Thus, we carried out a systematic review and meta-analysis of prospective cohort studies that investigated the association between coffee consumption and the risk of HCC or CLD. We separately estimated the relative risk (RR) of the two conditions, for regular, low, and high consumption compared with no or occasional coffee consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
75
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 47 publications
3
75
0
4
Order By: Relevance
“…To elucidate this issue, five systematic reviews or meta-analyses have been published7891035. In a meta-analysis of four cohort and 5 case-control studies, Larsson et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To elucidate this issue, five systematic reviews or meta-analyses have been published7891035. In a meta-analysis of four cohort and 5 case-control studies, Larsson et al .…”
Section: Discussionmentioning
confidence: 99%
“…performed an updated meta-analysis of cohort studies and observed a 15% decreased risk in liver cancer for an increment of 1 cup of coffee per day35. In a model comparing regular, low, and high consumption with no or occasional coffee consumption, the pooled RRs with 95 CIs were 0.66 (0.55–0.78) for regular, 0.78 (0.66–0.91) for low, and 0.50 (0.43–0.58) for high coffee consumption, respectively 35. Compared with previous meta-analyses, our study had two major strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Increased consumption of tea and coffee, two of the most popular beverages worldwide, has been associated with decreased risk of cancers of several sites in human studies. [1][2][3][4][5][6][7][8][9][10] Less is known about the association between tea or coffee consumption and risk of glioma, a cancer for which few lifestyle factors have been identified. 11,12 Coffee is a rich source of caffeine, and both tea and coffee contain additional biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiologic studies have evaluated the association between increased coffee consumption and reduced cancer risk. Also, several recent meta-analyses show a positive effect of coffee consumption on preventing liver cancer [10], endometrial cancer [11], and oral cancer [7]. …”
Section: Introductionmentioning
confidence: 99%